Corrigendum to “Comparative genomics of Cladosporium reveals limited evidence of selective pressure in soils historically contaminated with hexachlorocyclohexane and polychlorinated biphenyls” [J. Environ. Chem. Eng. 14(2)] - Giampiero De Simone; Elena Andreotti; Nicola Bertelloni; Laurence Fraissinet-Tachet; Thibault Le Gratiet; David Chapulliot; Janice Bamforth; Sean Walkowiak; Giulio Petroni; David Levin; Simona Di Gregorio (Journal of Environmental Chemical Engineering, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Comparative genomics of Cladosporium reveals limited evidence of selective pressure in soils historically contaminated with hexachlorocyclohexane and polychlorinated biphenyls - Giampiero De Simone; Elena Andreotti; Nicola Bertelloni; Laurence Fraissinet-Tachet; Thibault Le Gratiet; David Chapulliot; Janice Bamforth; Sean Walkowiak; Giulio Petroni; David Levin; Simona Di Gregorio (Journal of Environmental Chemical Engineering, 2026)

Denim Dream: Recycling Post-Consumer Jeans into Low-Density Water-Repellent Cellulose Foams - David Uslar; Hans Priks; Karl Jakob Levin; Lancy Peter Lopes; Tarmo Tamm (Circular Economy and Sustainability, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Novel genomically engineered antibiotic-free whole-cell biocatalysts for PET hydrolysis and waste remediation - Katherine Romero-Orejon; Hamid Reza Karbalaei-Heidari; Nediljko Budisa; David B. Levin (Journal of Hazardous Materials, 2026)

Micro- and Nanoplastics in the Human Brain: Mechanistic Plausibility, Translational Challenges, and Links to Neurological Disease Trends - Farshid Ghiyamihoor; Azam Asemi Rad; Parya Hassanifar; Raj Kaur; Janvi Hitenkumar Patel; Ian Kim; Asghar Marzban; Mehdi Mehdizadeh; David B. Levin; Saeid Ghavami; Antoniya Toncheva; Samira Benali; et al. (Molecular Neurobiology, 2026)

Your brain doesn’t look a day past 70! Cross-sectional associations with brain-predicted age in the cognitively-intact oldest-old - Mark K. Britton; Hannah Hoogerwoerd; Joshua Juhasz; Keyanni Joy Johnson; Paul D. Stewart; Pradyumna K. Bharadwaj; Stacy S. Merritt; Cortney J. Jessup; Clinton B. Wright; G. Alex Hishaw; David A. Raichlen; Victor A. Del Bene; et al. (GeroScience, 2025)
The cognitively-intact oldest-old (85 +) may be the most-resilient members of their birth cohort; due to survivorship effects (e.g., depletion of susceptibles), risk factors associated with brain aging biomarkers in younger samples may not generalize to the cognitively-intact oldest-old. We evaluated associations between established aging-related risk factors and brain-predicted age difference (brainPAD) in a cross-sectional cognitively-intact oldest-old sample. Additionally, we evaluated brainPAD-cognition associations to characterize brain maintenance vs. cognitive reserve in our sample. Oldest-old adults (N = 206; 85–99 years; Montreal Cognitive Assessment > 22 or neurologist evaluation) underwent T1-weighted MRI; brainPAD was generated with brainageR, such that more-positive brainPAD reflected more-advanced brain aging. Sex, education, alcohol and smoking history, exercise history, BMI, cardiovascular and metabolic disease history, and anticholinergic medication burden were self-reported. Global cognitive z-score and coefficient of variation were derived from the UDS 3.0 cognitive battery; crystallized-fluid discrepancy was derived from the NIH Toolbox Cognitive Battery. Mean brainPAD was -7.99 (SD: 5.37; range: -24.50, 6.03). Women showed more-delayed brain aging than men (B = -2.9, 95% CI = -4.6, -1.1, p = 0.002). No other exposures were significantly associated with brainPAD. BrainPAD was not associated with any cognitive variable. These findings suggest that cognitively-intact oldest-old adults may be atypically-resistant to risk factors associated with aging in younger samples, consistent with survivorship effects in aging. Furthermore, brainPAD may have limited explanatory value for cognitive performance in cognitively-intact oldest-old adults, potentially due to high cognitive reserve. Overall, our findings highlight the impact of survivorship effects on brain aging research. Graphical Abstract

Nature-inspired biodegradation of poly(butylene succinate-co-adipate): the potential of Cladosporium psychrotolerans isolated from marine copepods - Luca Niccolini; Giampiero De Simone; Maurizia Seggiani; Niccoletta Barbani; Damiano Rossi; Miriam Cappello; David Levin; Federica Spina; Xiaojun Yan; Giulio Petroni; Isabella Buttino; Simona Di Gregorio (Environmental Science and Pollution Research, 2025)

Insights into the antioxidant activity of carotenoid standards, microalgal, and yeast extracts via spectroscopic and electrochemical methods - Ana Carolina Mendes Hacke; Quintin Litke; Ryan Sestric; Bruce Hardy; Sabine Kuss; Song Liu; David Levin; John L. Sorensen (Food Chemistry, 2025)

Evaluation of low-density polyethylene degradation using a new thermophilic bacterial isolate - Mateus Manabu Abe; Carlos Eduardo Moraes; Marcos Vinícius Basaglia; Lívia Garcia Gonçalves; Roberta Nocelli; Sidney Souza dos Santos; Caio Felipe Cavicchia Zamuner; Elizabeth Brennan; Sílvia Helena Prado Bettini; Michelle Leali Costa; Marcia Cristina Branciforti; Marcia Regina de Moura Aouada; et al. (Science of The Total Environment, 2025)

Variation in estimates of the footprint of large, ground-mounted photovoltaic solar energy in the United States and its associated land-cover change across three datasets - Michael O. Levin; Emma Forester; Elizabeth L. Kalies; Lauren Goodman; Jason S. Hagani; Chevon C. Holmes; Noah Z. Krasner; Caitlin Markus; Jared B. Meek; Anubhav Vanamamalai; Shivani Agarwal; Uzma Ashraf; et al. (Journal of Environmental Management, 2025)

Nutrient analysis and response surface methodology reveal essential nutrient requirements for biomass production and astaxanthin synthesis in Phaffia rhodozyma - Ryan Sestric; Ana Carolina Mendes Hacke; John Sorensen; David B. Levin (Bioresource Technology Reports, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Opportunities and constraints of implementing the 3–30–300 rule for urban greening - Danial Owen; Alice Fitch; David Fletcher; Julius Knopp; Gregor Levin; Kate Farley; Ellen Banzhaf; Marianne Zandersen; Gwendoline Grandin; Laurence Jones (Urban Forestry & Urban Greening, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Rethinking plastic recycling: A comparison between North America and Europe - Joe Ackerman; David B. Levin (Journal of Environmental Management, 2023)

Associations between physical exercise type, fluid intelligence, executive function, and processing speed in the oldest-old (85 +) - Brian Duy Ho; Joseph M. Gullett; Stephen Anton; Mary Kathryn Franchetti; Pradyumna K. Bharadwaj; David A. Raichlen; Gene E. Alexander; Tatjana Rundek; Bonnie Levin; Kristina Visscher; Adam J. Woods; Ronald A. Cohen (GeroScience, 2023)

Algae-Based Two-Stage Supply Chain with Co-Products - Ruslana Rachel Palatnik; Mikhail Freer; Mark Levin; Alexander Golberg; David Zilberman (Ecological Economics, 2023)

Catalytic aerobic desulfurization of fuels in the presence of nanosized mixed carbide FeWC - Argam V. Akopyan; Ekaterina A. Eseva; Raman A. Mnatsakanyan; David A. Davtyan; Maxim O. Lukashov; Ivan S. Levin; Alexey A. Sadovnikov; Alexander V. Anisimov; Anna M. Terzyan; Artur M. Agoyan; Eduard Karakhanov (Chemical Engineering Journal, 2023)

Detecting hydrologic distinctions among Andean lakes using clumped and triple oxygen isotopes - Sarah A. Katz; Naomi E. Levin; Donald T. Rodbell; David P. Gillikin; Phoebe G. Aron; Benjamin H. Passey; Pedro M. Tapia; Analucía R. Serrepe; Mark B. Abbott (Earth and Planetary Science Letters, 2023)

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Marine phytoplankton resilience may moderate oligotrophic ecosystem responses and biogeochemical feedbacks to climate change - Adam C. Martiny; George I. Hagstrom; Tim DeVries; Robert T. Letscher; Gregory L. Britten; Catherine A. Garcia; Eric Galbraith; David Karl; Simon A. Levin; Michael W. Lomas; Allison R. Moreno; David Talmy; et al. (Limnology and Oceanography, 2022)
Are the oceans turning into deserts? Rising temperature, increasing surface stratification, and decreasing vertical inputs of nutrients are expected to cause an expansion of warm, nutrient deplete ecosystems. Such an expansion is predicted to negatively affect a trio of key ocean biogeochemical features: phytoplankton biomass, primary productivity, and carbon export. However, phytoplankton communities are complex adaptive systems with immense diversity that could render them at least partially resilient to global changes. This can be illustrated by the biology of the Prochlorococcus “collective.” Adaptations to counter stress, use of alternative nutrient sources, and frugal resource allocation can allow Prochlorococcus to buffer climate‐driven changes in nutrient availability. In contrast, cell physiology is more sensitive to temperature changes. Here, we argue that biogeochemical models need to consider the adaptive potential of diverse phytoplankton communities. However, a full understanding of phytoplankton resilience to future ocean changes is hampered by a lack of global biogeographic observations to test theories. We propose that the resilience may in fact be greater in oligotrophic waters than currently considered with implications for future predictions of phytoplankton biomass, primary productivity, and carbon export.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Finding incident cancer cases through outpatient oncology clinic claims data and integration into a state cancer registry - Christopher R. Cogle; Gary Levin; David J. Lee; Steven Peace; Megsys C. Herna; Jill MacKinnon; Clement K. Gwede; Celeste Philip; Tara Hylton (Cancer Causes & Control, 2021)

The Origin of NOAA’s Integrated Ecosystem Assessment Program: A Retrospective and Prospective - Chris J. Harvey; David L. Fluharty; Michael J. Fogarty; Phillip S. Levin; Steven A. Murawski; Franklin B. Schwing; Rebecca L. Shuford; Christopher R. Kelble; Mark E. Monaco (Coastal Management, 2021)

University Stormwater Management within Urban Environmental Regulatory Regimes: Barriers to Progressivity or Opportunities to Innovate? - Gregory Pierce; Kyra Gmoser-Daskalakis; Kelsey Jessup; Stanley B. Grant; Andrew Mehring; Brandon Winfrey; Megan A. Rippy; David Feldman; Patricia Holden; Richard Ambrose; Lisa Levin (Environmental Management, 2021)

Reproductive incompatibility between Amblyomma maculatum (Acari: Ixodidae) group ticks from two disjunct geographical regions within the USA - Michelle E. J. Allerdice; Alyssa N. Snellgrove; Joy A. Hecht; Kris Hartzer; Emma S. Jones; Brad J. Biggerstaff; Shelby L. Ford; Sandor E. Karpathy; Jesus Delgado-de la Mora; David Delgado-de la Mora; Jesus D. Licona-Enriquez; Jerome Goddard; et al. (Experimental and Applied Acarology, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Blunted cardiac output response to exercise in adolescents born preterm - Kristin Haraldsdottir; Andrew M. Watson; David F. Pegelow; Mari Palta; Laura H. Tetri; Taylor Levin; Melissa D. Brix; Ryan M. Centanni; Kara N. Goss; Marlowe M. Eldridge (European Journal of Applied Physiology, 2020)

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

Degradation of BTEX mixture by a new Pseudomonas putida strain: role of the quorum sensing in the modulation of the upper BTEX oxidative pathway - Ilaria Chicca; Simone Becarelli; Christopher Dartiahl; Salvatore La China; Teresa De Kievit; Giulio Petroni; Simona Di Gregorio; David B. Levin (Environmental Science and Pollution Research, 2020)

FreeSurfer 5.3 versus 6.0: are volumes comparable? A Chronic Effects of Neurotrauma Consortium study - Erin D. Bigler; Marc Skiles; Benjamin S. C. Wade; Tracy J. Abildskov; Nick J. Tustison; Randall S. Scheibel; Mary R. Newsome; Andrew R. Mayer; James R. Stone; Brian A. Taylor; David F. Tate; William C. Walker; et al. (Brain Imaging and Behavior, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

A metabolic and genomic assessment of sugar fermentation profiles of the thermophilic Thermotogales, Fervidobacterium pennivorans - Scott Wushke; Brian Fristensky; Xiang Li Zhang; Vic Spicer; Oleg V. Krokhin; David B. Levin; Matthew B. Stott; Richard Sparling (Extremophiles, 2018)

The role of dissolved oxygen content as a modulator of microbial polyhydroxyalkanoate synthesis - Warren Blunt; Richard Sparling; Daniel J. Gapes; David B. Levin; Nazim Cicek (World Journal of Microbiology and Biotechnology, 2018)

A preliminary report of cerebral white matter microstructural changes associated with adolescent sports concussion acutely and subacutely using diffusion tensor imaging - Trevor Wu; Tricia L. Merkley; Elisabeth A. Wilde; Amanda Barnes; Xiaoqi Li; Zili David Chu; Stephen R. McCauley; Jill V. Hunter; Harvey S. Levin (Brain Imaging and Behavior, 2018)

Description of a cryptic thermophilic (pro)phage, CBP1 from Caldibacillus debilis strain GB1 - Scott Wushke; Zimo Jin; Victor Spicer; Xiang Li Zhang; Brian Fristensky; Oleg V. Krokhin; David B. Levin; Richard Sparling (Extremophiles, 2018)

Ecological bias in environmental health studies: the problem of aggregation of multiple data sources - Rakefet Shafran-Nathan; Ilan Levy; Noam Levin; David M. Broday (Air Quality, Atmosphere & Health, 2017)

Microbial eukaryotic distributions and diversity patterns in a deep‐sea methane seep ecosystem - Alexis L. Pasulka; Lisa A. Levin; Josh A. Steele; David H. Case; Michael R. Landry; Victoria J. Orphan (Environmental Microbiology, 2016)
Summary Although chemosynthetic ecosystems are known to support diverse assemblages of microorganisms, the ecological and environmental factors that structure microbial eukaryotes (heterotrophic protists and fungi) are poorly characterized. In this study, we examined the geographic, geochemical and ecological factors that influence microbial eukaryotic composition and distribution patterns within H ydrate R idge, a methane seep ecosystem off the coast of O regon using a combination of high‐throughput 18S rRNA tag sequencing, terminal restriction fragment length polymorphism fingerprinting, and cloning and sequencing of full‐length 18S rRNA genes. Microbial eukaryotic composition and diversity varied as a function of substrate (carbonate versus sediment), activity (low activity versus active seep sites), sulfide concentration, and region ( N orth versus S outh H ydrate R idge). Sulfide concentration was correlated with changes in microbial eukaryotic composition and richness. This work also revealed the influence of oxygen content in the overlying water column and water depth on microbial eukaryotic composition and diversity, and identified distinct patterns from those previously observed for bacteria, archaea and macrofauna in methane seep ecosystems. Characterizing the structure of microbial eukaryotic communities in response to environmental variability is a key step towards understanding if and how microbial eukaryotes influence seep ecosystem structure and function.

Hydrothermal Vents and Methane Seeps: Rethinking the Sphere of Influence - Lisa A. Levin; Amy R. Baco; David A. Bowden; Ana Colaco; Erik E. Cordes; Marina R. Cunha; Amanda W. J. Demopoulos; Judith Gobin; Benjamin M. Grupe; Jennifer Le; Anna Metaxas; Amanda N. Netburn; et al. (Frontiers in Marine Science, 2016)

Whole exome sequence analysis of Peters anomaly - Eric Weh; Linda M. Reis; Hannah C. Happ; Alex V. Levin; Patricia G. Wheeler; Karen L. David; Erin Carney; Brad Angle; Natalie Hauser; Elena V. Semina (Human Genetics, 2014)

Microbial abundance and diversity patterns associated with sediments and carbonates from the methane seep environments of Hydrate Ridge, OR - Jeffrey J. Marlow; Joshua A. Steele; David H. Case; Stephanie A. Connon; Lisa A. Levin; Victoria J. Orphan (Frontiers in Marine Science, 2014)

Resource limitation in a competitive context determines complex plant responses to experimental resource additions - Caroline E. Farrior; David Tilman; Ray Dybzinski; Peter B. Reich; Simon A. Levin; Stephen W. Pacala (Ecology, 2013)
Almost all models of plant resource limitation are grounded in either one or both of two simple conceptual models: Liebig's Minimum Hypothesis (LMH), the idea that plants are limited by the resource in shortest supply, and the Multiple Limitation Hypothesis (MLH), the idea that plants should adjust to their environment so that all essential resources are equally limiting. Despite the differences in their predictions, experiments have so far failed to discriminate between them. In a simple factorial nitrogen and water addition experiment in a Minnesota grassland, we observed shifts in allocation that, as in previous studies, are not all explained by a single theory. We found that leaf biomass responded positively to nitrogen additions but did not respond to water additions. We found that fine‐root biomass increased in response to water additions, but only at low nitrogen levels, and that fine‐root biomass decreased in response to nitrogen additions, but only at high water levels. To understand these responses we built a physiologically based model of plant competition for water, nitrogen, and space to predict plant allocation to fine roots and leaves. Critically, we include in our model the inherent variability of soil moisture and treat light, water, and nitrogen as resources with distinct mechanistic roles. Experimental results showed that plants were nitrogen and water limited. The model explains the experimental results, under conditions of co‐limitation, as follows. Foliage increases with nitrogen additions but not water additions because leaf construction is constrained by nitrogen uptake. When water is added, plants spend a larger fraction of the growing season limited by light (and effectively nitrogen) than by water. Thus, water additions cause fine‐root biomass to increase because of the increased importance of nitrogen limitation. The response of fine‐root biomass to water additions decreases with nitrogen additions because these additions reduce nitrogen limitation. In general, our results are explained by sequential resource limitation. The rate of carbon assimilation may be limited by a single resource at any one moment, but the identity of the limiting resource(s) changes throughout the growing season.

Developing and Implementing an Advanced Communication Training Program in Oncology at a Comprehensive Cancer Center - Carma L. Bylund; Richard F. Brown; Philip A. Bialer; Tomer T. Levin; Barbara Lubrano di Ciccone; David W. Kissane (Journal of Cancer Education, 2011)

Association between cervical dysplasia and human papillomavirus in HIV seropositive women from Johannesburg South Africa - Cynthia Firnhaber; Hoa Van Le; Audrey Pettifor; Doreen Schulze; Pam Michelow; Ian M. Sanne; David A. Lewis; Anna-Lise Williamson; Bruce Allan; Sophia Williams; Allen Rinas; Simon Levin; et al. (Cancer Causes & Control, 2010)

Results from a prostate cancer admixture mapping study in African-American men - Cathryn Hufford Bock; Ann G. Schwartz; Julie J. Ruterbusch; Albert M. Levin; Christine Neslund-Dudas; Susan J. Land; Angela S. Wenzlaff; David Reich; Paul McKeigue; Wei Chen; Elisabeth I. Heath; Isaac J. Powell; et al. (Human Genetics, 2009)

Seizure Detection Using Seizure Probability Estimation: Comparison of Features Used to Detect Seizures - Levin Kuhlmann; Anthony N. Burkitt; Mark J. Cook; Karen Fuller; David B. Grayden; Linda Seiderer; Iven M. Y. Mareels (Annals of Biomedical Engineering, 2009)

Are adolescents more vulnerable to drug addiction than adults? Evidence from animal models - Nicole L. Schramm-Sapyta; Q. David Walker; Joseph M. Caster; Edward D. Levin; Cynthia M. Kuhn (Psychopharmacology, 2009)

In vitro culture of Lambdina fiscellaria lugubrosa nucleopolyhedrovirus in heterologous cell lines - Beatrixe H. Whittome-Waygood; John C. Fraser; Christopher J. Lucarotti; Imre S. Otvos; Nicholas Conder; David B. Levin (In Vitro Cellular & Developmental Biology - Animal, 2009)

Diversity in Current Ecological Thinking: Implications for Environmental Management - Susan A. Moore; Tabatha J. Wallington; Richard J. Hobbs; Paul R. Ehrlich; C. S. Holling; Simon Levin; David Lindenmayer; Claudia Pahl-Wostl; Hugh Possingham; Monica G. Turner; Mark Westoby (Environmental Management, 2009)

Pyruvate catabolism and hydrogen synthesis pathway genes of Clostridium thermocellum ATCC 27405 - Carlo R. Carere; Vipin Kalia; Richard Sparling; Nazim Cicek; David B. Levin (Indian Journal of Microbiology, 2008)

Colorectal cancer screening perceptions and practices: Results from a national survey of gastroenterology, surgery and radiology trainees - Amy S. Oxentenko; Robert A. Vierkant; Darrell S. Pardi; David R. Farley; Eric J. Dozois; Thomas E. Hartman; David M. Hough; Wesley O. Petersen; Carrie N. Klabunde; Katherine Sharpe; John H. Bond; Robert A. Smith; et al. (Journal of Cancer Education, 2007)

Consumption, Investment, and Future Well‐Being: Reply to Daly et al. - KENNETH J. ARROW; GRETCHEN DAILY; PARTHA DASGUPTA; PAUL EHRLICH; LAWRENCE GOULDER; GEOFFREY HEAL; SIMON LEVIN; KARL‐GÖRAN MÄLER; STEPHEN SCHNEIDER; DAVID STARRETT; BRIAN WALKER (Conservation Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Salmonid Opsin Sequences Undergo Positive Selection and Indicate an Alternate Evolutionary Relationship in Oncorhynchus - David B. Levin; Stephen G. Dann; W. Ted Allison; John S. Taylor; Craig W. Hawryshyn (Journal of Molecular Evolution, 2004)

Identification of epistatic interaction affecting glycoalkaloid content in tubers of tetraploid potato (Solanum tuberosum L.) - Jacob van Dam; Ilan Levin; Paul C. Struik; David Levy (Euphytica, 2003)

Chronic inhibition of α4β2 nicotinic receptors in the ventral hippocampus of rats: impacts on memory and nicotine response - David Arthur; Edward Levin (Psychopharmacology, 2002)

The Function of Marine Critical Transition Zones and the Importance of Sediment Biodiversity - Lisa A. Levin; Donald F. Boesch; Alan Covich; Cliff Dahm; Christer Erséus; Katherine C. Ewel; Ronald T. Kneib; Andy Moldenke; Margaret A. Palmer; Paul Snelgrove; David Strayer; Jan Marcin Weslawski (Ecosystems, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Genetic characterisation of tetraploid potato (Solanum tuberosum L.) emphasising genetic control of total glycoalkaloid content in the tubers - Jacob van Dam; Ilan Levin; Paul C. Struik; David Levy (Euphytica, 1999)